An Intriguing Case of Erythroderma Possibly Related to Psoriasis Vulgaris - Earlia, Nanda; Umborowati, Menul Ayu; Tasrif, Aqil Yuniawan; Pradistha, Aldilla; Liana, Mahda Rizki; Bulqiah, Mikyal (Indonesian Journal of Case Reports, 2023)
Erythroderma or generalized exfoliating dermatitis is an inflammatory disease characterized by erythema and thickened scales. A woman, 34 years old, was consulted with complaints of red spots accompanied by blisters and peeling skin almost all over her body for 4 days. Complaints are accompanied by itching and burning sensations. The patient had experienced complaints like this 5 months ago and had been treated at three different hospitals. Physical examination found in the facial region, thorax, superior and inferior right and left extremities, erythematous patches with diffuse borders, thick scales, erosions, and a generalized distribution. The patient's fingernails were found to have a change in shape (pitting nails). Examination of the ANA profile was negative, IgE atopy did not show an allergic reaction to a specific allergen, and histopathological examination was within normal limits. The patient was diagnosed with erythroderma based on psoriasis vulgaris. Treatment includes injection of methylprednisolone, cetirizine 10 mg tablets, and wound care with wet gauze and topical cream. After giving therapy, the patient's clinical improvement. Erythroderma occurs because of an underlying condition and cannot be prevented by itself. Erythroderma because of an underlying inflammatory skin condition usually resolves with treatment but can recur at any time. Overall, the prognosis for erythroderma depends on the underlying cause and is generally good if the underlying disease can be treated effectively.